Substance use behaviours and the UK furlough scheme: evidence from eight longitudinal population surveys. (20th October 2021) - Green, M; Di Gessa, G; Maddock, J; Parsons, S; Wielgoszewska, B; Stevenson, AJ; Griffith, GJ; Booth, C; Croft, J; Ploubidis, GB
Abstract: Disruptions to economic activity such as job loss can impact substance use behaviours. During the COVID-19 pandemic many countries implemented a furlough scheme to prevent job loss. We examine how furlough was associated with respondents' substance use behaviours in the initial stages of the pandemic in the UK. Data were from over 27, 000 participants in eight adult longitudinal surveys. Participants self-reported economic activity (furlough or job loss vs stable employment) and smoking (any current), vaping (any current) and drinking alcohol (>4 days/week or 5+ drinks per typical occasion) both before and during the initial stages of the pandemic. Changes in frequency/quantity of substance use were also examined. Risk ratios were estimated within each study using modified Poisson regression, adjusting for a range of potential confounders, including pre-pandemic behaviour (though this was excluded in analyses of behaviour change). Findings were synthesised using a random effects meta-analysis. Compared to stable employment, participation in the furlough scheme was associated with smoking (risk ratio: 1.24 [95% CI: 1.08-1.42]; I2=0%) while job loss was associated with vaping (1.72 [1.10-2.71]; I2=25%) and heavier drinking (1.21 [1.02-1.43]; I2=2%), but these associations were largely accounted for by confounders (adjusted risk ratios: smoking: 1.06 [0.96-1.16]; I2=8%; vaping: 1.55 [0.93-2.56]; I2=42%; and drinking: 1.03 [0.89-1.20]; I2=35%). Furlough was associated with drinking more than before the pandemic (adjusted risk ratio: 1.15 [1.00-1.33]; I2=70%), and with increases in vaping behaviour (1.54 [1.14-2.07]; I2=0%). Increased drinking associated with furlough is concerning, while increased vaping likely represents moves to reduce smoking and may be positive.